The Theoretical and Methodological Opportunities Afforded by Guided Play With Young Children - Yu, Yue; Shafto, Patrick; Bonawitz, Elizabeth; Yang, Scott C.-H.; Golinkoff, Roberta M.; Corriveau, Kathleen H.; Hirsh-Pasek, Kathy; Xu, Fei (Frontiers in Psychology, 2018)
For infants and young children, learning takes place all the time and everywhere. How children learn best both in and out of school has been a long-standing topic of debate in education, cognitive development, and cognitive science. Recently, guided play has been proposed as an integrative approach for thinking about learning as a child-led, adult-assisted playful activity. The interactive and dynamic nature of guided play presents theoretical and methodological challenges and opportunities. Drawing upon research from multiple disciplines, we discuss the integration of cutting-edge computational modeling and data science tools to address some of these challenges, and highlight avenues towards an empirically grounded, computationally precise and ecologically valid framework of guided play.